Paediatric to adult healthcare transition in resource-limited settings: a narrative review - Christiana M Russ; Nirmala Priya Narla; Leah Ratner; Fernanda Viera Bastos; Sheila Agyeiwaa Owusu; Angela Osei-Bonsu (BMJ Publishing Group, 2021)
Background Ageing into adulthood is challenging at baseline, and doing so with a chronic disease can add increased stress and vulnerability. Worldwide, a substantial care gap exists as children transition from care in a paediatric to adult setting. There is no current consensus on safe and equitable healthcare transition (HCT) for patients with chronic disease in resource-denied settings. Much of the existing literature is specific to HIV care. The objective of this narrative review was to summarise current literature related to adolescent HCT not associated with HIV, in low-income and middle-income countries (LMICs) and other resource-denied settings, in order to inform equitable health policy strategies.Methods A literature search was performed using defined search terms in PubMed and Cumulative Index to Nursing and Allied Health Literature databases to identify all peer-reviewed studies published until January 2020, pertaining to paediatric to adult HCT for adolescents and young adults with chronic disease in resource-denied settings. Following deduplication, 1111 studies were screened and reviewed by two independent reviewers, of which 10 studies met the inclusion criteria. Resulting studies were included in thematic analysis and narrative synthesis.Results Twelve subthemes emerged, leading to recommendations which support equitable and age-appropriate adolescent care. Recommendations include (1) improvement of community health education and resilience tools for puberty, reproductive health and mental health comorbidities; (2) strengthening of health systems to create individualised adolescent-responsive policy; (3) incorporation of social and financial resources in the healthcare setting; and (4) formalisation of institution-wide procedures to address community-identified barriers to successful transition.Conclusion Limitations of existing evidence relate to the paucity of formal policy for paediatric to adult transition in LMICs for patients with childhood-onset conditions, in the absence of a diagnosis of HIV. With a rise in successful treatments for paediatric-onset chronic disease, adolescent health and transition programmes are needed to guide effective health policy and risk reduction for adolescents in resource-denied settings.